Socialization Of Stem Learning Models For Teachers - Mesterjon Mesterjon; Dwi Rulismi; Agus Firnandi; Selpia Juliansyah; Dendi Sapril (Jurnal Dehasen Untuk Negeri, 2023)
The role of the teacher in every learning activity in schools is very important. The teacher is responsible for the success of each learning activity that has been designed. There is a tendency for teachers who are not optimal in preparing measurable designs and lesson plans that will have an impact on learning activities that are not optimal and tend not to be in accordance with learning outcomes. So that in providing socialization material for this service, we are a Collaborative Team of Lecturers and Students who have conducted Tripmen and equipped the teacher council with materials and direct practice in designing learning materials and we have also provided assistance in implementing the STEM learning model for teachers with the aim of providing education to MTS teachers regarding STEM learning. STEM learning model socialization activities for teachers are carried out by presenting material presentations and practicing designing learning materials. After following the material carefully, teachers generally and measurably already have and have acquired new knowledge related to the STEM learning model. That way, for future sustainability, the motivation of the teacher council will emerge by itself to prepare well in advance related to the learning material to be discussed, this can provide the best knowledge and insight for students, especially when interacting with students of higher quality. than before.